2009
DOI: 10.1016/j.ijrobp.2008.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Biological Image-Guided Radiotherapy in Rectal Cancer: Challenges and Pitfalls

Abstract: Integration of MRI and FDG-PET into radiotherapy seems feasible. Gradient-based segmentation is recommended for FDG-PET. Spatial variance between MRI and FDG-PET TVs should be taken into account for target definition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…These studies have common steps that are discussed below by tumor location: specimen fixation (for all except one), registration of the specimen with the images, and deformation corrections for some of them (Table 2). Such are the PSPVs generated by Daisne et al [25], Caldas-Magalhaes et al [26], Stroom et al [27], Van Loon et al [28], Yu et al [29], Meng et al [30], Schaefer et al [31], Dahele et al [32], Wanet et al [33], Zhang et al [34], and Roels et al [35]. After this, we provide an overview of the volumetric studies.…”
Section: Available Data Setsmentioning
confidence: 94%
See 2 more Smart Citations
“…These studies have common steps that are discussed below by tumor location: specimen fixation (for all except one), registration of the specimen with the images, and deformation corrections for some of them (Table 2). Such are the PSPVs generated by Daisne et al [25], Caldas-Magalhaes et al [26], Stroom et al [27], Van Loon et al [28], Yu et al [29], Meng et al [30], Schaefer et al [31], Dahele et al [32], Wanet et al [33], Zhang et al [34], and Roels et al [35]. After this, we provide an overview of the volumetric studies.…”
Section: Available Data Setsmentioning
confidence: 94%
“…Threshold [27-29, 33, 43] Adaptive threshold [12,31,33,52] Gradient [47] Fuzzy C-means [48] Active contours [49] FLAB [54] Neural network [55] Multimodality using level sets [51] Cervical cancer Threshold [34] Colon, rectal and sigmoid cancer Threshold [39,45] Adaptive threshold [35,44] Gradient [35,39] multimodality segmentation tool using level sets and Jensen-Renyi divergence (JRD). They compared the results to those from Zaidi et al [50], and found that the JRD approach was second to the FCM-SW method.…”
Section: Evaluation Of Pet Segmentation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cannon 20 showed that "Demons"-based deformable registration improved the accuracy, compared with rigid registration, in assessment of tumour response with SUV peak and VOI 50% in head and neck cancer. Roels et al 21 investigated the use of MRI and 18 F-FDG-PET/CT for rectal tumour response to CRT. Images acquired before, during and after CRT from 15 patients were registered using B-spline registration with mutual information as similarity metric.…”
Section: Deformable Registrationmentioning
confidence: 99%
“…Apart from the various applications of FDG PET/CT listed above, there are many other utilities of FDG PET/CT. For example, it can be used for radiation oncology purposes [9][10][11][12], e.g. by identifying areas with high metabolic activity that may require a boost of radiation to improve treatment outcome.…”
mentioning
confidence: 99%